Area Identification Of Catchment Areas Using Far Sensing And Gis Applications In East Jakarta - Himmes Fitra Yuda; Afiat Anugrahadi; Puspita Dinda Rahmawati (Journal of Geoscience Engineering & Energy (JOGEE), 2021)
The presence of catchment areas is needed. Besides its function for groundwater conservation, this area also is used to reduce flood risks. The need for houses also encourages people to use qualified Catchment areas to be used as houses and does not consider its natural factors. It happens a lot in suburban areas such as East Jakarta that in early 2020 this area becomes one of the most affected areas due to the flood in DKI Jakarta. Due to the world pandemic, Covid-19, direct field research is hard to carry out, so this research using remote sensing applications and geographic information systems to identify areas that qualify as water catchment areas. In practice, it uses secondary data sourced from national institutions and agencies with direct access to the data. The results showed that 12,36% of the research areas did not meet the requirements as Catchment areas, 68,01% were sufficiently eligible, and 19,63% were highly qualified. However, in its utilization, only 22.06% of the total research area currently plays an active role as groundwater catchment areas because of the land cover dominated by built-up land. It can lead to various risks as flooding or a reduction in the volume of groundwater.